Jealousy in “Sarapalha” - Abriata, Vera Lucia Rodella; Carmelino, Ana Cristina (Laboratório Editorial FCL-UNESP, 2008)
The object of analysis of this paper is the study of 'jealousy', a passion manifested in the tale "Sarapalha", by João Guimarães Rosa. The theoretical presuppositions were taken from French Semiotics. We aim at describing the syntactic dimension of jealousy that manifests the intensity of the passion-affected subjects' - Cousin Ribeiro and Cousin Argemiro - suffering from the loss of the beloved subject object, Cousin Luíza, to a shared rival. We also try to describe the canonical sequence of jealousy in the enunciative scene that pictures the moment Argemiro reveals Ribeiro his platonic love nurtured toward Luíza. Ribeiro, a jealous person, marked by exclusive attachment, takes the role of the socialappraiser observer and does not forgive Argemiro, to whom is imputed the role of a rival by Ribeiro's construction of imagination.